Black First-Year College Students' Alcohol Outcome Expectancies. Issue 2 (3rd March 2020) - Thorpe, Shemeka; Tanner, Amanda E.; Ware, Samuella; Guastaferro, Kate; Milroy, Jeffrey J.; Wyrick, David L.
ABSTRACT: Background : Alcohol outcome expectancies (AOEs) are associated with college students' varied alcohol consumption. Existing research on AOEs focuses primarily on heterosexual White students. Thus, it is important to explore how the intersection of multiple identities such as race, gender, and sexual orientation influence the endorsement of specific AOEs. Purpose : This paper examines AOEs among Black first-year college students, with specific attention to the influence of gender and sexual orientation. Methods : Participants were 307 Black students from four universities in the United States. We conducted bivariate analyses using the 2-factor and 4-factor B-CEOA scale. Results : Most students did not hold positive AOEs such as tension reduction and sexual enhancement. Students were more likely to endorse negative AOEs such as behavioral and cognitive impairment and social risk. Discussion : Black first-year college students reported more negative expectations associated with alcohol use, including those related to negative social risks and consequences. Thus, AOEs may serve as a protective factor against alcohol use among Black college students. Translation to Health Education Practice : Alcohol interventions should be tailored to focus on the intersection of race, gender, and sexual orientation. Culturally relevant alcohol interventions have the potential to reduce the immediate and long-term consequences of alcohol use.